2005
DOI: 10.1111/j.1523-1755.2005.09916.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and the progression of renal disease in chronic renal failure patients

Abstract: Dyslipidemia is a common complication of progressive kidney disease and contributes to the high cardiovascular morbidity and mortality of chronic kidney disease (CKD) patients. Recent evidence also suggests a role for dyslipidemia in the development and progression of renal disease. Experimental studies have demonstrated that lipids may induce glomerular and tubulointerstitial injury, and that lipid-lowering treatments ameliorate renal injury. Various lipid abnormalities have been associated with the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
131
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 71 publications
3
131
0
Order By: Relevance
“…These metabolic, cellular and vascular effects can lead to endothelial dysfunction with cardiorenal manifestations [38,39]. In light of this, there is some preliminary evidence supporting additive effects of RAS inhibition and lipid lowering on reducing the rate of decline of renal function [40].…”
Section: Effects Of Genotypes and Phenotypes On Renal Functionmentioning
confidence: 99%
“…These metabolic, cellular and vascular effects can lead to endothelial dysfunction with cardiorenal manifestations [38,39]. In light of this, there is some preliminary evidence supporting additive effects of RAS inhibition and lipid lowering on reducing the rate of decline of renal function [40].…”
Section: Effects Of Genotypes and Phenotypes On Renal Functionmentioning
confidence: 99%
“…Patients with CKD often have lipid abnormalities. CKD is associated with dysregulation in high density lipoprotein (HDL) and triglyceride metabolism (1,2). Therefore in the plasma of these patients, the level of triglyceride-rich lipoproteins is increased considerably.…”
mentioning
confidence: 99%
“…Therefore in the plasma of these patients, the level of triglyceride-rich lipoproteins is increased considerably. Moreover, some alterations occurred in composition of these lipoproteins (1,2). Lipid abnormalities in CKD patients increase the risk of cardiovascular diseases in CKD patients (1,2).…”
mentioning
confidence: 99%
“…Dyslipidemia is reported to be a common complication of progressive kidney disease [27]. Several studies have shown hypercholesterdemia and hypertriglycerdemia to be the risk factors for renal failure [23].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia is the most common plasma lipid abnormality in patients with renal failure [25,26]. Dyslipdemia is a common complication of progressive kidney disease which also contributes to high cardiovascular morbidity and mortality of renal disease patients [27].…”
Section: Introductionmentioning
confidence: 99%